Ubiquitous Computing Developing and Evaluating Near Field Communication Applications - Resatsch, Florian; SpringerLink (Online service) (Wiesbaden : Gabler, 2010)
Near Field Communication (NFC) technology has become increasingly important for ubiquitous computing. Florian Resatsch investigates the optimal strategies for developing and evaluating ubiquitous computing applications based on NFC. He draws on a variety of current theories on ubiquitous computing, human-computer interaction, and technology acceptance to propose an iterative process model (UCAN) for the integrated development and evaluation of NFC applications. Finally, the author offers a range of design guidelines for NFC applications in four categories: NFC technology, tag infrastructure, devices, and human factors.
Theoretical Framework -- Human Computer Interaction and Technology Acceptance -- Designing an Ubiquitous Computing Application Development and Evaluation Process Model (UCAN) -- From Initial Idea to Low-Fidelity Prototype: Easymeeting and the Mobile Prosumer -- Working Prototype: An NFC-based Mobile Phone Ticketing System -- Conclusion, Limitations, and Future Research.
Keywords: Economics; Management information systems; Economics/Management Science; Business Information Systems